The Development of Science Mobile Learning Media to Improve Primary Students Learning Achievements (Universitas Negeri Semarang, 2019)
The development of science mobile learning is based on school condition which is lack of the use of technology. The lack of creativity and the uses of technology influencing study environment in class and has an effect in the student's result. So, it is needed to create some innovation in term of choose and use media. This research's goal is to enhance student's achievements. The type of research that used in this study is research and development (R & D). The stages in this research is used ADDIE (Analysis, Design, Develop, Implementation, and Evaluation). The research was carried out at SDN 2 Bobos & SDN 1 Cangkoak. For the test use n-gain test. Based on n-gain calculation, it show that the small sample obtain 0.61 and for the large sample reach 0.57, both in moderate categories. It can be conclude that science mobile learning can enhance student's study result achievements.